Tracing enhances problem‐solving transfer, but without effects on intrinsic or extraneous cognitive load. Issue 6 (4th September 2020) - Ginns, Paul; Hu, Fang‐Tzu; Bobis, Janette
Summary: People can make pointing gestures and tracing actions with the index finger with little or no conscious effort. From the perspective of cognitive load theory, such "biologically primary" gestures and actions might help people learn "biologically secondary" concepts and skills requiring extended cognitive effort, such as reading, science, or mathematics. Studies on tracing or tracing and pointing have yielded mixed findings regarding hypothesized effects on intrinsic and extraneous cognitive load. The present study investigated whether computer‐based instructions to trace elements of worked examples on angle relationships would affect school students' ( N = 106) self‐reports of intrinsic and extraneous cognitive load, as well as problem‐solving transfer test performance. The tracing effect on transfer posttests seen in prior studies was replicated, but cognitive load hypotheses were not supported. Implications for educational practice and future research are discussed.